Pencegahan Fraud melalui Perilaku Etis dan Budaya Organisasi: Mediasi Pengendalian Internal, Moderasi Religiositas pada Niat Whistleblowing - Lucy Chairoel; Lasti Yossi Hastini; Mellyna Eka Yan Fitri (Journal of Economics and Management Scienties, 2026)
Fraud prevention is a crucial aspect in maintaining the operational integrity of an organization, especially in sectors that handle sensitive information or financial resources. Fraud prevention strategies are crucial for protecting assets, ensuring regulatory compliance, and maintaining a company's reputation. The objectives of this study are to examine the influence of whistleblowing intention, ethical behavior, and organizational culture on fraud prevention, to examine the influence of religiosity as a moderator on the relationship between whistleblowing intention and fraud prevention, and to examine the influence of internal control mediating variables on the relationship between organizational culture and fraud prevention. The study used a quantitative approach with a survey method involving 100 employees as respondents. The research instrument was a questionnaire that had been tested for validity and reliability, with data analysis conducted using the Partial Least Square (PLS) method is used to examine the relationship between variables. The results of the analysis showed that whistleblowing intention, ethical behavior, and religiosity had a significant effect on fraud prevention. Organizational culture had no significant effect on fraud prevention. Organizational culture had a significant effect on internal control. The moderating variable, religiosity, did not strengthen or weaken the effect of whistleblowing intention on fraud prevention. The mediating variable of internal control does not significantly influence organizational culture indirectly on fraud prevention. The findings of this study highlight the importance of management for fraud prevention, the need for whistleblowing procedures in the form of SOPs, the ethical value of each policy, and increasing religiosity by providing worship facilities in the work environment.